An Evaluation of Nurses' Perception and Confidence After Implementing a Workplace Aggression and Violence Prevention Training Program. (April 2020) - Story, Angela R.; Harris, Robin; Scott, Susan D.; Vogelsmeier, Amy
Abstract : Workplace violence is highly prevalent for nurses, often going unreported. Regrettably, the very patients and visitors being cared for often perpetrate the majority of violence. This article's purpose is to describe how an institution implemented a workplace violence prevention training program designed to increase nurses' perception and confidence with aggressive and violent events. Evaluation of this quality improvement program posttraining was positive, suggesting this approach may influence nurses' abilities to prevent and manage these events. Abstract : Supplemental digital content is available in the text.